A model for gauging the prominence of web-based CSR disclosure. Issue 4 (7th November 2016) - Chong, Sabrina; Ali, Irshad; Lodhia, Sumit K.
Abstract : Purpose: The purpose of this paper is to introduce a model to assess web-based corporate social responsibility (CSR) disclosure prominence and use this model to explore the prominence of CSR disclosures of listed New Zealand (NZ) companies. Design/methodology/approach: A CSR Disclosure Prominence Indicator Model was constructed using five key elements that include the dissemination medium, accessibility, location, content variety and extent of CSR disclosures. The websites of 65 of the largest listed NZ companies from 11 industry groupings were explored through this model. Findings: A significant proportion (81.5 per cent) of listed NZ companies in the sample were utilising their websites for communicating CSR information to stakeholders. The CSR Disclosure Prominence Indicator Model revealed that companies that have CSR-related disclosures on their websites used multiple dissemination media and locations to enhance prominence of such disclosures. CSR commentary on the webpage was the most prominent dissemination medium due to its ease of accessibility, with a separate CSR webpage being the most prominent location. Environmental performance and society-related issues received the most prominent emphasis. Although companies from "sensitive" industry sectors appeared to disclose their CSR information more prominently, those from "less sensitive" industries also attempted to make their CSR disclosure more prominent and noticeable through strategic placement and through the extent of disclosure. Research limitations/implications: The paper highlights the importance of managing web-based CSR disclosure prominence, thereby highlighting its significance in communication of CSR information. Practical implications: Prominently placed CSR disclosures could be a significant platform for companies to strategically manage their image and identity. The CSR Disclosure Prominence Indicator Model could be utilised by companies to effectively assess and manage the prominence of CSR disclosures on their websites for more effective communication with stakeholders. Originality/value: The paper complements earlier studies on CSR disclosures by constructing and applying a model to assess the prominence of web-based CSR disclosures.